1995
DOI: 10.1021/j100029a005
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Ultrafast Dynamics of Reactions. 10. Molecular Dynamics Studies of Dissociation, Recombination, and Coherence

Abstract: In this paper, the molecular dynamics of dissociation and recombination of iodine in argon clusters are reported and compared with the experimental results of the preceding paper et al. J. Phys. Chem. 1995, 99, 11309). The microscopic processes of bond breakage and bond reformation are visualized with the help of simple classical models. The coherent recombination observed experimentally is shown to be closely related to the coherent nature of bond breakage and the homogeneity of local structures in large cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 6 publications
2
49
0
Order By: Relevance
“…8 Fluorescence spectroscopy is often used to identify the products of photochemical reactions in clusters, [9][10][11][12][13][14][15][16][17][18][19] and femtosecond laser excitation provides information on the time evolution of reactions. 20,21 Femtosecond photoelectron spectroscopy on mass selective iodine Ar anion clusters showed that a solvation shell of 20 Ar atoms was sufficient to induce recombination of the iodine fragments 21,20 and similar experiments on iodine in neutral Ar clusters revealed that caging was completed within 10 −12 s. [22][23][24] A thorough investigation of the cage effect of hydrogen halides doped into the interior or onto the surface of clusters and aligned in a static electric and a laser field was recently undertaken by Buck and co-workers. [25][26][27][28][29][30] They measured the kinetic energy of the hydrogen atom as a function of the orientation and showed that the dissociation of hydrogen halides can even be inhibited on the cluster surface because the light hydrogen carries almost all the kinetic energy and is caged by the cluster and the heavy halogen atom.…”
Section: Introductionmentioning
confidence: 98%
“…8 Fluorescence spectroscopy is often used to identify the products of photochemical reactions in clusters, [9][10][11][12][13][14][15][16][17][18][19] and femtosecond laser excitation provides information on the time evolution of reactions. 20,21 Femtosecond photoelectron spectroscopy on mass selective iodine Ar anion clusters showed that a solvation shell of 20 Ar atoms was sufficient to induce recombination of the iodine fragments 21,20 and similar experiments on iodine in neutral Ar clusters revealed that caging was completed within 10 −12 s. [22][23][24] A thorough investigation of the cage effect of hydrogen halides doped into the interior or onto the surface of clusters and aligned in a static electric and a laser field was recently undertaken by Buck and co-workers. [25][26][27][28][29][30] They measured the kinetic energy of the hydrogen atom as a function of the orientation and showed that the dissociation of hydrogen halides can even be inhibited on the cluster surface because the light hydrogen carries almost all the kinetic energy and is caged by the cluster and the heavy halogen atom.…”
Section: Introductionmentioning
confidence: 98%
“…7,8,9 Dissociation takes place when the potential between two atoms of an oxygen molecule exceeds some critical value. The point at which this occurs is relatively ambiguous because it is difficult to explicitly define the point on the Morse potential curve where the molecule dissociates.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…To account for this, the atoms' velocities are scaled to adjust their kinetic energy to match the change in potential so the total energy of the system remains constant. 7 Subsequently, as the atoms move with their new velocities, they affect their neighbors. In the case of recombination, the energy released by the creation of an oxygen molecule is transferred to the surrounding atoms by this process.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Vibrational energy relaxation of diatomic molecules in matrix environment has been studied in great detail. [8][9][10] The HONO system has been studied intensively both theoretically 6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23] and experimentally. [3][4][5][24][25][26][27][28][29] Neither experimental 30 nor theoretical 12,20 studies could find the reaction taking place in the gas phase with significant yields; hence, isomerization seems to be facilitated by the dissipative forces of the matrix environment.…”
Section: Introductionmentioning
confidence: 99%